A COMPARATIVE STUDY ON THE EFFECTIVENESS OF ADDING ROSEMARY AND GINGER EXTRACTS ON MEAT QUALITY DURING FREEZING STORAGE - & Alkass, Baker (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
The aim of the this experiment was to determine the effect of adding rosemary (0.05%)and ginger extracts (0.5%) on microbial and oxidative stability in meat lamb stored at -18º c for 150 days. Results revealed that there is steady rise (p<0.01) in microbial count and oxidative rancidity in untreated and treated samples with increasing storage period up to 150 days .Also , a significant (P≤0.01) reduction in all bacteria count (P≤0.01) ,TBA was observed in samples treated with ginger or rosemary extracts as compared with untreated samples .It was noticed that addition of ginger extract is more effective against formation of TBA than rosemary extract, however no difference exist between them on antimicrobial agent.